MAGES 4.0: Accelerating the world's transition to VR training and democratizing the authoring of the medical metaverse - Zikas, Paul; Protopsaltis, Antonis; Lydatakis, Nick; Kentros, Mike; Geronikolakis, Stratos; Kateros, Steve; Kamarianakis, Manos; Evangelou, Giannis; Filippidis, Achilleas; Grigoriou, Eleni; Angelis, Dimitris; Tamiolakis, Michail; et al. (IEEE computer graphics and applications, 2023)
In this work, we propose MAGES 4.0, a novel Software Development Kit (SDK) to accelerate the creation of collaborative medical training applications in VR/AR. Our solution is essentially a low-code metaverse authoring platform for developers to rapidly prototype high-fidelity and high-complexity medical simulations. MAGES breaks the authoring boundaries across extended reality, since networked participants can also collaborate using different virtual/augmented reality as well as mobile and desktop devices, in the same metaverse world. With MAGES we propose an upgrade to the outdated 150-year-old master-apprentice medical training model. Our platform incorporates, in a nutsell, the following novelties: a) 5G edge-cloud remote rendering and physics dissection layer, b) realistic real-time simulation of organic tissues as soft-bodies under 10ms, c) a highly realistic cutting and tearing algorithm, d) neural network assessment for user profiling and, e) a VR recorder to record and replay or debrief the training simulation from any perspective.